Penentuan Dosis Terbaik Koagulan Aluminium Sulfat Dalam Mengolah Limbah Cair Laboratorium Dengan Proses Koagulasi Dan Flokulasi - Ferizal Nuurfath; Shinta Elystia; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The wastewater of Fundamental Chemical Laboratory contained very high concentration of TSS and TDS. Therefore, wastewater treatment is needed before discharge to the environment. Coagulation process is able to destablilize the particles in the wastewater to form a floc, formed floc will unite and become a larger floc through the flocculation process so it can settle. This research aim to determine the best dose of aluminium sulfate in reducing concentration of TSS and TDS. Variation of the aluminium sulfate coagulant dose is 1, 2, 3, and 4 gr/L. Based on the result, the best dose in reducing concentration of TSS and TDS was 3 gr/L with removal efficiency of TSS 78,61% and TDS 62,02%.Keywords : Aluminium Sulfate, Coagulation, Flocculation, TSS, TDS, Laboratory Watewater.